2021
DOI: 10.1177/1063426620982624
|View full text |Cite
|
Sign up to set email alerts
|

Childhood ADHD Symptoms in Relation to Trauma Exposure and PTSD Symptoms Among College Students: Attending to and Accommodating Trauma

Abstract: Attention-deficit/hyperactivity disorder (ADHD) and posttraumatic stress disorder (PTSD) are highly comorbid among children and adolescents with a history of maltreatment and trauma. This comorbidity is linked to increased symptom severity and poor academic and social outcomes. Such negative outcomes are shown to have further negative outcomes during the college years. However, research has yet to directly examine the associations between ADHD, trauma exposure, and PTSD among college students. To address this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Some responding bodies do stress the issue of bullying and harassment as a crucial factor for school's failures towards neurodivergent pupils. This is in line with research stressing high risk of neurodivergent student being victims of bullying at school (Wiener & Mak, 2008), as well as increased risk of mental illness, such as PTSD and depression due to traumahaving negative impact on the academic performance of neurodivergent people (Miodus et al, 2021). In comparison with other Swedish disability rights movements and the Swedish queer movement, Swedish neurodivergent self-advocacy, outside of parent and professional dominated movements, has only recently started to emerge (Bertilsdotter Rosqvist et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation

Waiting for Discovery and Support?

Österborg Wiklund,
Bertilsdotter Rosqvist,
Bagger
et al. 2023
EJIE
“…Some responding bodies do stress the issue of bullying and harassment as a crucial factor for school's failures towards neurodivergent pupils. This is in line with research stressing high risk of neurodivergent student being victims of bullying at school (Wiener & Mak, 2008), as well as increased risk of mental illness, such as PTSD and depression due to traumahaving negative impact on the academic performance of neurodivergent people (Miodus et al, 2021). In comparison with other Swedish disability rights movements and the Swedish queer movement, Swedish neurodivergent self-advocacy, outside of parent and professional dominated movements, has only recently started to emerge (Bertilsdotter Rosqvist et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
“…In the case of SC, bullying and harassment is seen as a barrier to learning and development. Despite research specifying the risk of bullying and harassment of neurodivergent pupils, with the consequences of trauma for mental health, school results and later work life (Miodus et al, 2021;Wiener & Mak, 2008), this is not mentioned as a reason for school failure in the case of neurodivergence. The memorandum stresses the importance of knowledge about not only NPS, but also the 'consequences' of neurobiological impairments: "Pupils who, as a result of an impairment, have difficulties fulfilling the knowledge requirements or requirement levels that exist, must be given support that aims to as far as possible counteract the consequences of the impairment" (Ministry of Education and Research, 2020a, p. 19), as if the consequences derive from the impairments in itself, not necessarily from the clash with a disabling environment.…”
Section: Neurodivergence As School Failurementioning
confidence: 99%

Waiting for Discovery and Support?

Österborg Wiklund,
Bertilsdotter Rosqvist,
Bagger
et al. 2023
EJIE
“…TF-CBT not only reduces the psychosocial difficulties of children who have endured childhood adversity and trauma, but it may also substantially improve these children's resilience [54]. According to the study [55], college students with a history of elevated ADHD symptoms in childhood reported significantly more trauma exposure and PTSD symptoms. These findings have implications for clinical interventions with children and adolescents, college counseling, and accessibility services related to psychological health and academic accommodations.…”
Section: Resultsmentioning
confidence: 99%
“…Students with ADHD had significantly higher PTSD scores. Individuals with ADHD have been found to have higher rates of traumatic exposure, often making a diagnosis complicated (Miodus et al, 2021). Emerging evidence indicates that the pandemic has been traumatic and may lead to PTSD symptoms (Bridgland et al, 2021;Lahav, 2020;Sibley et al, 2021), and one could argue that some of these overlapping symptoms could have been captured in the elevated PTSD scores.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates an overlap between ADHD and PTSD symptoms, such as disorganization and dysregulation (Martínez et al, 2016;Miodus et al, 2021). Although the relationship remains unclear, studies show that children and adults diagnosed with ADHD are at elevated risk for exposure to traumatic events and may develop PTSD-related symptoms (Barkley, 2010;Siegfried et al, 2016).…”
Section: Adhd and The Covid-19 Pandemicmentioning
confidence: 99%